A Church for Scotland? The Free Church and Scottish Nationalism after the Disruption. Issue 1 (April 2020) - Mallon, Ryan
Abstract : The 1843 Disruption of the Church of Scotland, which split the national church in two, was one of the most important events in Victorian Britain. The evangelical ministers who seceded from the Kirk to form the Free Church of Scotland did so in protest against the British state's intrusion in the church's affairs. The anti-English and patriotic rhetoric of the Disruption has led historians such as David Bebbington to argue that it represented something close to a nationalist movement. This paper questions this claim by assessing the nationalist characteristics of the Disruption and their role in shaping the political 'unionist-nationalism' of the mid-nineteenth century. It examines the kind of nationalist sentiment, if any, evident at the Disruption, the role of Free Church members in the National Association for the Vindication of Scottish Rights, the short-lived proto-nationalist pressure group, and the nationalism of the Free Church minister James Begg, who called for Home Rule for Scotland in 1850. By assessing the influence of the Disruption's constructionist critique of the union on political nationalism, the paper argues that the religious nationalism evident in 1843 failed to translate to a political context in the mid-nineteenth century. The new religiously pluralist environment of the post-Disruption period saw the Free Church turn inwards and begin to focus upon its own denominational fortunes as a single Scottish national identity was replaced by a variety of competing confessional identities, each with their own claim to nationhood.